KiDS + GAMA: constraints on horndeski gravity from combined large-scale structure probes - Spurio Mancini, Alessio; Schäfer, Björn Malte (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We present constraints on Horndeski gravity from a combined analysis of cosmic shear, galaxy-galaxy lensing and galaxy clustering from $450\, \mathrm
Gesehen am 12.02.2020